E-health: Determinants, opportunities, challenges and the way forward for countries in the WHO African Region - Gatwiri Doris; Seddoh Anthony; Kirigia Joses M; Muthuri Lenity HK; Seddoh Janet (BMC, 2005)
Abstract Background The implementation of the 58th World Health Assembly resolution on e-health will pose a major challenge for the Member States of the World Health Organization (WHO) African Region due to lack of information and communications technology (ICT) and mass Internet connectivity, compounded by a paucity of ICT-related knowledge and skills. The key objectives of this article are to: (i) explore the key determinants of personal computers (PCs), telephone mainline and cellular and Internet penetration/connectivity in the African Region; and (ii) to propose actions needed to create an enabling environment for e-health services growth and utilization in the Region. Methods The effects of school enrolment, per capita income and governance variables on the number of PCs, telephone mainlines, cellular phone subscribers and Internet users were estimated using a double-log regression model and cross-sectional data on various Member States in the African Region. The analysis was based on 45 of the 46 countries that comprise the Region. The data were obtained from the United Nations Development Programme (UNDP), the World Bank and the International Telecommunications Union (ITU) sources. Results There were a number of main findings: (i) the adult literacy and total number of Internet users had a statistically significant (at 5% level in a t-distribution test) positive effect on the number of PCs in a country; (ii) the combined school enrolment rate and per capita income had a statistically significant direct effect on the number of telephone mainlines and cellular telephone subscribers; (iii) the regulatory quality had statistically significant negative effect on the number of telephone mainlines; (iv) similarly, the combined school enrolment ratio and the number of telephone mainlines had a statistically significant positive relationship with Internet usage; and (v) there were major inequalities in ICT connectivity between upper-middle, lower-middle and low income countries in the Region. By focusing on the adoption of specific technologies we attempted to interpret correlates in terms of relationships instead of absolute "causals". Conclusion In order to improve access to health care, especially for the majority of Africans living in remote rural areas, there is need to boost the availability and utilization of e-health services. Thus, universal access to e-health ought to be a vision for all countries in the African Region. Each country ought to develop a road map in a strategic e-health plan that will, over time, enable its citizens to realize that vision.